A study on the genus Anthaxia (Merocratus) Bílý 1989 (Coleoptera: Buprestidae: Anthaxiini) - Bílý, Svatopluk; Plachetka, Mikuláš (Zootaxa, 2019)
Description of four new species: Anthaxia (Merocratus) angustata Bílý, sp. nov. (Vietnam), A. (M.) priska Bílý, sp. nov. (Indonesia: Kalimantan), A. (M.) violaceidorsis Bílý, sp. nov. (Indonesia: Kalimantan), and A. (M.) lucifera Plachetka, sp. nov. (The Philippines). Two species-groups are defined within the subgenus: A. (M.) insulaecola Obenberger, 1944 species-group and A. (M.) tricolor Kerremans, 1912 species-group. The sexual dimorphism of certain species is discussed and the distribution of some species are modified including new state records. All new species are illustrated and compared with the most related species.